Trabajadoras del sector de la limpieza: precariedad en el empleo, desigualdades temporales y división sexual del trabajo - Guy Lebeer; Esteban Martinez (Universidade do Porto, 2012)
Based on the results of a qualitative study conducted in several sites where the Belgian cleaning service providers operate, this article shows the importance of gender inequalities in the sector and decomposes the mechanisms related to the specific work regimes and to the specific modalities of work organization and manpower management. This study also brings to light that women's employment in such activity registers the effects of a double segregation: first of all, a segregation related to the particular conditions of subordination which characterize the cleaning work, performed more and more often within the framework of subcontracting relations and, then, a segregation ensuing from the tensions which affect particularly the women, on the one hand non-negotiable work regimes and working schedules - compulsory part-time work and segmented and shifted schedules - and on the other hand the constraints of the private life.